ANALYSIS OF ECONOMIC CONFLICT BETWEEN THE COMMUNITY WITH PALM OIL PLANT COMPANY (Study of Supreme Court Decision Number: 152 PK / TUN / 2015 in Kecamatan Kubu Kabupaten Kubu Raya) - DOMINIKUS ARIF, SH NPM. A2021141095, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis analyzes land conflicts between communities and oil palm plantation companies (Study on Supreme Court Decision Number: 152 PK / TUN / 2015 in Kecamatan Kubu Kabupaten Kubu Raya). The approach method used in this research is sociological normative approach. From the result of this thesis research, it can be concluded that the Supreme Court Judges Rejected the Request of Review of PT.Sintang Raya In the Supreme Court Decision Number: 152 PK / TUN / 2015.On the Supreme Court ruling, which granted the citizens' claim to restore the overlapping areas. What Factors That Cause Land Conflicts In Oil Palm Plantations Between Communities With PT. Sintang Raya Kubu Sub-district of Kubu Raya Regency is the occurrence of various conflicts between local communities and plantation companies both regarding community land and plantation development for the community, conflict overlapping land among palm oil plantation companies, and conflicts between plantation land and mining area. The existence of overlapping land among palm oil plantation companies. Efforts that must be done by the National Land Agency (BPN) Kubu Raya cancel the certificate of Right to Business PT. Sintang Raya, by refusing the submission of a review (PK) filed by PT. Sintang Raya then obtains a permanent legal force (Inkracht Van Gewijsde). And do the Execution. Recommendation: Land Agency Immediately Cancel Certificate of Right to Use Business PT. Sintang Raya. Execute with the attendance of the judges of the State Administrative Court of Pontianak, the police officers, the Village Head, the community, and the land parties that border on each other.Keywords: Conflict, Land, Plantation, Oil Palm.2ABSTRAKTesis ini analisa konflik pertanahan antara masyarakat dengan perusahaan perkebunan kelapa sawit (Studi Terhadap Putusan Mahkamah Agung Nomor: 152 PK/TUN/2015 di Kecamatan Kubu Kabupaten Kubu Raya). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan normatif sosiologis. Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Majelis Hakim Mahkamah Agung Menolak Permohonan Peninjauan Kembali PT.Sintang Raya Dalam Putusan Mahkamah Agung Nomor :152 PK/TUN/2015. Pada putusan Mahkamah Agung, yang mengabulkan gugatan warga untuk mengembalikan areal yang tumpang tindih itu. Faktor-Faktor Apa Yang Menyebabkan Terjadinya Konflik Pertanahan Di Perkebunan Kelapa Sawit Antar Masyarakat Dengan PT. Sintang Raya Kecamatan Kubu Kabupaten Kubu Raya yaitu terjadinya berbagai konflik antara masyarakat setempat dengan perusahaan perkebunan baik menyangkut lahan masyarakat maupun pembangunan perkebunan untuk masyarakat ,konflik tumpang tindih lahan antar sesama perusahan perkebunan sawit, dan konflik antara lahan perkebunan dengan areal pertambangan. Adanya tumpang tindih lahan antar sesama perusahan perkebunan sawit.Upaya yang harus dilakukan oleh Badan Pertanahan Nasional (BPN) Kubu Raya membatalkan sertifikat Hak Guna Usaha PT. Sintang Raya, dengan menolak pengajuan peninjauan kembali (PK) yang diajukan oleh PT. Sintang Raya maka memperoleh kekuatan hukum tetap (Inkracht Van Gewijsde). Dan melakukukan Eksekusi. Rekomendasi : Badan Pertanahan segera Membatalkan Sertipikat Hak Guna Usaha PT. Sintang Raya. Melakukan Eksekusi dengan di hadiri hakim pengadilan Tata Usaha Negara Pontianak, aparat Kepolisian, Kepala Desa, masyrakat, dan para pihak tanah yang saling berbatasan.Kata Kunci: Konflik, Pertanahan, Perkebunan, Kelapa Sawit.